"Chemistry-on-the-complex": functional RuII polypyridyl-type sensitizers as divergent building blocks. (24th September 2018) - Mede, Tina; Jäger, Michael; Schubert, Ulrich S.
Abstract : Ruthenium polypyridyl type complexes are potent photoactive compounds, and have found – among others – a broad range of important applications in the fields of biomedical diagnosis and phototherapy, energy conversion schemes such as dye-sensitized solar cells (DSSCs) and molecular assemblies for tailored photo-initiated processes. Abstract : Ruthenium polypyridyl type complexes are potent photoactive compounds, and have found – among others – a broad range of important applications in the fields of biomedical diagnosis and phototherapy, energy conversion schemes such as dye-sensitized solar cells (DSSCs) and molecular assemblies for tailored photo-initiated processes. In this regard, the linkage of Ru II polypyridyl-type complexes with specific functional moieties is highly desirable to enhance their inherent photophysical properties, e.g., with a targeting function to achieve cell selectivity, or with a dye or redox-active subunits for energy- and electron-transfer. However, the classical approach of performing ligand syntheses first and the formation of Ru complexes in the last steps imposes synthetic limitations with regard to tolerating functional groups or moieties as well as requiring lengthy convergent routes. Alternatively, the diversification of Ru complexes after coordination (termed "chemistry-on-the-complex") provides an elegant complementary approach. In addition to the Click chemistry concept, the rapidly developing synthesis and purification methodologies permit the preparation of Ru conjugates via amidation, alkylation and cross-coupling reactions. In this regard, recent developments in chromatography shifted the limits of purification, e.g., by using new commercialized surface-modified silica gels and automated instrumentation. This review provides detailed insights into applying the "chemistry-on-the-complex" concept, which is believed to stimulate the modular preparation of unpreceded molecular assemblies as well as functional materials based on Ru-based building blocks, including combinatorial approaches.